30. EFFECT OF DEHEMA ON REDUCING SWELLING, BRUISES IN SOFT TISSUE INJURY MODEL (Vietnam Journal of Community Medicine, 2025)
DEHEMA is an herbal product developed from an ancient remedy prescribed for pain, swelling, and bruises caused by injury.Objectives: Evaluate the anti-swelling, anti-bruises effects of DEHEMA in soft tissue injuries model.Method: Rabbits were subjected to soft tissue trauma to the ears and administered with two doses of DEHEMA (6 ml/kg/day or 12 ml/kg/day) or Celecoxib 24 mg/kg/day for 10 consecutive days. The lesions on the rabbit ears were observed, and the thickness of the rabbit ears and the area of ​​the lesions were measured.Results: DEHEMA at both doses faster recovery damage, reduced bruising and congestion compared to the model group; reduced the thickness and area of ​​the damaged area in rabbits compared to the model group with statistical significance at the time points after 3-7 days (p < 0.05) and was not different from the group taking Celecoxib (p > 0.05).Conclusion: DEHEMA were effective in reducing swelling and bruises in the soft tissue injury model.
Keywords: DEHEMA; soft tissue injuries